An Inverted Sandwich Electrochromic Device Architecture Does Not Require Optically Transparent Electrodes. Issue 9 (31st July 2019) - Rozman, Martin; Gaberšček, Miran; Marolt, Gregor; Bren, Urban; Lukšič, Miha
Abstract: All currently known sandwich‐type electrochromic devices (ECDs) require at least one optically transparent electrode (OTE) for their operation. Here, it is demonstrated that this requirement is conceptually redundant. The so‐called inverted sandwich ECD architecture is introduced, with its principal components being: two solid optically nontransparent electrodes (high electrical conductivity material), an insulator that prevents a short‐circuit between the electrodes, and an electrochromic mixture applied on a solid carrier. The modus operandi of the present proof‐of‐concept solution‐phase double‐sided ECD is a reversible color change of the indicator dye caused by the variations in pH of the water‐based electrolyte solution due to electrolysis. Application of the inverted sandwich topology to make electrochromic tapes is given. Abstract : At present, all conventional electrochromic cell devices (ECDs) in a sandwich configuration use at least one optically transparent electrode. This study offers a general solution for a novel cell device topology—called the inverted sandwich—which involves only optically nontransparent electrodes. It represents a significant advance in understanding the correlation between ECD architectures and their functionality.